First report of Strongyloides sp. (Nematoda, Strongyloididae) in Leopardus tigrinus (Carnivora: Felidae) in the municipality of Botucatu, State of São Paulo, Brazil - Santos, Karina R. dos [UNESP]; Faciulli, Paula [UNESP]; Paparotto, Telma [UNESP]; Takahira, Regina Kiomi [UNESP]; Lopes, Raimundo Souza [UNESP]; Silva, Reinaldo J. da [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2009)
O presente estudo reporta o primeiro caso de infecção por Strongyloides sp. em Leopardus tigrinus no município de Botucatu, Estado de São Paulo, Brasil. Fezes do exemplar parasitado de L. tigrinus foram cultivadas em fezes eqüinas esterilizadas e foi realizada infecção experimental em gato (Felis catus domesticus) com três mil larvas L3 infectantes por via subcutânea, para a identificação da espécie de Strongyloides envolvida no parasitismo. As fêmeas partenogenéticas obtidas do animal experimental foram analisadas porém a comparação dos dados biométricos encontrados com os dados da literatura não permitiu a identificação da espécie. Este é o primeiro relato sobre a ocorrência de Strongyloides sp. em L. tigrinus

The present study reports the first case of infection by Strongyloides sp. in Leopardus tigrinus in the municipality of Botucatu, State of São Paulo, Brazil. Feces of the infected L. tigrinus specimen were cultivated in sterilized equine feces and a cat (Felis catus domesticus) was experimentally infected with three thousand infective L3 subcutaneous route, in order to identify the Strongyloides species involved in the parasitism. Parthenogenetic females recovered from the experimental animals were analyzed but comparison between the biometric data found and the data in the literature did not enable identification of the species. This is the first report on the occurrence of Strongyloides sp. in L. tigrinus.
Primeiro relato de Strongyloides sp. (Nematoda, Strongyloididae) em Leopardus tigrinus (Carnivora: Felidae) do município de Botucatu, Estado de São Paulo, Brasil
Keywords: Leopardus tigrinus; felídeos selvagens; infecção parasitária; doença; novo hospedeiro; Leopardus tigrinus; wild felids; parasitic infection; disease; new host